Lenvatinib versus sorafenib in first-line treatment of patients with unresectable hepatocellular carcinoma: a randomised phase 3 non-inferiority trial. Issue 10126 (24th March 2018) - Kudo, Masatoshi; Finn, Richard S; Qin, Shukui; Han, Kwang-Hyub; Ikeda, Kenji; Piscaglia, Fabio; Baron, Ari; Park, Joong-Won; Han, Guohong; Jassem, Jacek; Blanc, Jean Frederic; Vogel, Arndt; et al.
Summary: Background: In a phase 2 trial, lenvatinib, an inhibitor of VEGF receptors 1–3, FGF receptors 1–4, PDGF receptor α, RET, and KIT, showed activity in hepatocellular carcinoma. We aimed to compare overall survival in patients treated with lenvatinib versus sorafenib as a first-line treatment for unresectable hepatocellular carcinoma. Methods: This was an open-label, phase 3, multicentre, non-inferiority trial that recruited patients with unresectable hepatocellular carcinoma, who had not received treatment for advanced disease, at 154 sites in 20 countries throughout the Asia-Pacific, European, and North American regions. Patients were randomly assigned (1:1) via an interactive voice–web response system—with region; macroscopic portal vein invasion, extrahepatic spread, or both; Eastern Cooperative Oncology Group performance status; and bodyweight as stratification factors—to receive oral lenvatinib (12 mg/day for bodyweight ≥60 kg or 8 mg/day for bodyweight <60 kg) or sorafenib 400 mg twice-daily in 28-day cycles. The primary endpoint was overall survival, measured from the date of randomisation until the date of death from any cause. The efficacy analysis followed the intention-to-treat principle, and only patients who received treatment were included in the safety analysis. The non-inferiority margin was set at 1·08. The trial is registered withClinicalTrials.gov, numberNCT01761266 . Findings: Between March 1, 2013 and July 30, 2015, 1492 patients were recruited. 954 eligible patients were randomly assigned to lenvatinib (n=478) or sorafenib (n=476). Median survival time for lenvatinib of 13·6 months (95% CI 12·1–14·9) was non-inferior to sorafenib (12·3 months, 10·4–13·9; hazard ratio 0·92, 95% CI 0·79–1·06), meeting criteria for non-inferiority. The most common any-grade adverse events were hypertension (201 [42%]), diarrhoea (184 [39%]), decreased appetite (162 [34%]), and decreased weight (147 [31%]) for lenvatinib, and palmar-plantar erythrodysaesthesia (249 [52%]), diarrhoea (220 [46%]), hypertension (144 [30%]), and decreased appetite (127 [27%]) for sorafenib. Interpretation: Lenvatinib was non-inferior to sorafenib in overall survival in untreated advanced hepatocellular carcinoma. The safety and tolerability profiles of lenvatinib were consistent with those previously observed. Funding: Eisai Inc.